2019
DOI: 10.1186/s12964-019-0346-2
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen regulation of cardiac cAMP-L-type Ca2+ channel pathway modulates sex differences in basal contraction and responses to β2AR-mediated stress in left ventricular apical myocytes

Abstract: Backgrounds/Aim Male and female hearts have many structural and functional differences. Here, we investigated the role of estrogen (E2) in the mechanisms of sex differences in contraction through the cAMP-L-type Ca 2+ channel pathway in adult mice left ventricular (LV) apical myocytes at basal and stress state. Methods Isolated LV apical myocytes from male, female (Sham) and ovariectomised mice (OVX) were used to investigate contractility, Ca … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
35
1
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(44 citation statements)
references
References 53 publications
4
35
1
4
Order By: Relevance
“…The ability of G1 to restore these parameters suggest that chronic GPER activation re-sensitizes cardiac β-AR regulation in this HFpEF model (68). These data also mirror those reported in a study of the apical myocardium, in which expression of the Ca v 1.2α subunit and I Ca,L were lower in apical myocytes from male or OVX mice compared with sham female mice, and E 2 treatment of myocytes from OVX animals corrected these differences (72). The reduction in the amplitude of electrically stimulated Ca 2+ transients in myocytes isolated from OVX female mice were restored by G1, to an extent similar to that achieved with E 2 treatment.…”
Section: Effects Of Estrogen and Gper Activation On I Calsupporting
confidence: 87%
“…The ability of G1 to restore these parameters suggest that chronic GPER activation re-sensitizes cardiac β-AR regulation in this HFpEF model (68). These data also mirror those reported in a study of the apical myocardium, in which expression of the Ca v 1.2α subunit and I Ca,L were lower in apical myocytes from male or OVX mice compared with sham female mice, and E 2 treatment of myocytes from OVX animals corrected these differences (72). The reduction in the amplitude of electrically stimulated Ca 2+ transients in myocytes isolated from OVX female mice were restored by G1, to an extent similar to that achieved with E 2 treatment.…”
Section: Effects Of Estrogen and Gper Activation On I Calsupporting
confidence: 87%
“…High levels of catecholamines during stress impair left ventricular systolic function, which may lead to Takotsubo cardiomyopathy (TTC) (96,118). Along with other researchers, we found that E2/ERs reversed the decreased Ca 2ϩ transient amplitude in ventricular myocytes stimulated by high concentration of catecholamine, which restored myocardial contractility (17,54,69,135). Furthermore, Ma et al (68) reported that estrogen improved cardiac contractility and intracellular Ca 2ϩ transient amplitude in OVX rat models of ischemia-reperfusion treated with Iso.…”
Section: Estrogen and Myocardial Contractionsupporting
confidence: 75%
“…In female rabbit hearts, E2 upregulated I CaL and Ca v 1.2␣ protein levels through ER␣ via a regional genomic mechanism (144). In our recent study, we found that estrogen supplementation significantly increased I CaL , Ca v 1.2␣ mRNA, and protein levels in OVX mice cardiomyocytes compared with male and sham female cardiomyocytes (69). Elsewhere, estrogen increased I CaL and prolonged the plateau period of action potential, leading to a longer QT interval, an effect that increased the risk of LQT2 arrhythmia phenotype (19,27,53,84,94,115,144,145).…”
Section: Estrogen Regulates L-type Ca 2ϩ Channelmentioning
confidence: 89%
See 1 more Smart Citation
“…18 Údaje o pohlavních rozdílech v kontraktilitě myokardu se liší a byly nedávno shrnuty Machukim a spol. 19 Zatímco Schwertz a spol. 20,21 a Machuki a spol.…”
Section: Pohlavní Rozdíly V Normálním Myokarduunclassified